2018
DOI: 10.1111/lcrp.12144
|View full text |Cite
|
Sign up to set email alerts
|

Linking serial sexual offences: Moving towards an ecologically valid test of the principles of crime linkage

Abstract: Purpose To conduct a test of the principles underpinning crime linkage (behavioural consistency and distinctiveness) with a sample more closely reflecting the volume and nature of sexual crimes with which practitioners work, and to assess whether solved series are characterized by greater behavioural similarity than unsolved series. Method A sample of 3,364 sexual crimes (including 668 series) was collated from five countries. For the first time, the sample included solved and unsolved but linked‐by‐DNA sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…Many studies have examined case linkage accuracy of sexual assault using Jaccard's coefficients and ROC analysis (Bennell et al, 2009(Bennell et al, , 2010Mokros and Alison, 2002;Slater et al, 2015;Winter et al, 2013;Woodhams et al, 2007bWoodhams et al, , 2019Woodhams and Labuschagne, 2012). When assessing cross-crime similarity coefficients of linked and unlinked offence pairs, these researchers' Jaccard's coefficients for linked pairs ranged from 0.39 to 0.52 and unlinked pairs ranged from 0.17 to 0.34, supporting behavioural consistency.…”
Section: Linkage Of Sexual Assaultmentioning
confidence: 88%
See 4 more Smart Citations
“…Many studies have examined case linkage accuracy of sexual assault using Jaccard's coefficients and ROC analysis (Bennell et al, 2009(Bennell et al, , 2010Mokros and Alison, 2002;Slater et al, 2015;Winter et al, 2013;Woodhams et al, 2007bWoodhams et al, , 2019Woodhams and Labuschagne, 2012). When assessing cross-crime similarity coefficients of linked and unlinked offence pairs, these researchers' Jaccard's coefficients for linked pairs ranged from 0.39 to 0.52 and unlinked pairs ranged from 0.17 to 0.34, supporting behavioural consistency.…”
Section: Linkage Of Sexual Assaultmentioning
confidence: 88%
“…The past 15-20 years have seen case linkage research and practice flourish, with support for linkage practice found across high-volume offences, as well as interpersonal offences (Bennell et al, 2010(Bennell et al, , 2014Burrell and Bull, 2011;Grubin et al, 2001;Labuschagne, 2006;Santtila et al, 2008;Slater et al, 2015;Tonkin and Woodhams, 2017;Tonkin et al, 2011Tonkin et al, , 2012Winter et al, 2013;Woodhams et al, 2007bWoodhams et al, , 2019Woodhams and Labuschagne, 2012;Woodhams and Toye, 2007). As research and investigative methods continue to develop, specialised databases have been created to assist in the case linkage process, such as the Canadian Violent Crime Linkage Analysis System (ViCLAS), the Violent Criminal Apprehension Program of the United States of America (USA) and Australia's Violent and Sexual Crimes Database (VSCD).…”
Section: Case Linkagementioning
confidence: 99%
See 3 more Smart Citations